Correction: Direct characterization of graphene doping state by in situ photoemission spectroscopy with Ar gas cluster ion beam sputtering. Issue 4 (5th January 2018) - Yun, Dong-Jin; Kim, Seyun; Jung, Changhoon; Lee, Chang-Seok; Sohn, Hiesang; Won, Jung Yeon; Kim, Yong Su; Chung, JaeGwan; Heo, Sung; Kim, Seong Heon; Seol, Minsu; Shin, Weon Ho
Abstract : Correction for 'Direct characterization of graphene doping state by in situ photoemission spectroscopy with Ar gas cluster ion beam sputtering' by Dong-Jin Yun et al., Phys. Chem. Chem. Phys., 2018, 20, 615–622.